Effect of Chlordiazepoxide or Haloperidol Oral Premedication during Midazolam-Ketamine Anaesthesia on Physiological and Blood Gas Parameters in Adult Male Bonnet Macaques (Macaca radiata): Effect of Chlordiazepoxide or Haloperidol Oral Premedication during Midazolam-Ketamine Anaesthesia on Physiological and Blood Gas Parameters in Adult Male Bonnet Macaques (Macaca radiata) (Indonesian Journal of Primatology, 2024)
Capturing wild animals with minimal stress is crucial to reduce morbidity and mortality. Oral premedicants can ease handling and subsequent anaesthetic administration. This study evaluated anaesthetic protocols and physiological changes during vasectomy in 12 adult male Bonnet Macaques. Group I received 10 mg/kg chlordiazepoxide, and Group II received 1 mg/kg haloperidol orally four hours before midazolam-ketamine anaesthesia. Sedation quality, induction, maintenance, and recovery were assessed. Physiological and blood gas changes were monitored at 0, 5, 10, 15, and 20 minutes. Both groups exhibited sedation post-premedication. Induction, maintenance, and anaesthesia depth were similar. Group I had better analgesia, while Group II had superior muscle relaxation. Blood gas analysis indicated mild stress and respiratory acidosis in both groups, with Group II showing more significant hypoxemia and respiratory acidosis. Haloperidol-premedicated animals were easier to handle but exhibited increased stress parameters compared to chlordiazepoxide-premedicated animals. Recovery was better in Group I. Both protocols effectively induced sedation and anaesthesia in Bonnet Macaques.